What Is at Stake with Decolonizing Design? A Roundtable. (2nd January 2018) - Schultz, Tristan; Abdulla, Danah; Ansari, Ahmed; Canlı, Ece; Keshavarz, Mahmoud; Kiem, Matthew; Martins, Luiza Prado de O.; J.S. Vieira de Oliveira, Pedro
Abstract: This roundtable was conducted by the eight founding members of Decolonising Design Group in October 2017, using an online messaging platform. Each member approached design and decoloniality from different yet interrelating viewpoints, by threading their individual arguments with the preceding ones. The piece thus offers and travels through a variety of subject matter including politics of design, artificiality, modernity, Eurocentrism, capitalism, Indigenous Knowledge, pluriversality, continental philosophy, pedagogy, materiality, mobility, language, gender oppression, sexuality, and intersectionality.